Aggravation and subsequent disappearance of cervical disc herniation after cervical open-door laminoplasty: A case report. Issue 10 (March 2018) - Meng, Yang; Wang, Xiaofei; Wang, Beiyu; Wu, Tingkui; Liu, Hao
Abstract: Rationale: Cervical open-door laminoplasty can enlarge the volume of the cervical vertebral canal and thus has become an effective and safe treatment for multilevel cervical disc herniation and cervical stenosis. Some post-surgery complications exist, such as reduction of cervical alignment and local kyphosis. However, aggravation of cervical disc herniation at the surgical level during short-term follow-up has not been discussed. Additionally, spontaneous disappearance of herniated disc pulposus is a common phenomenon in the lumbar region but is relatively rare in the cervical region. Patient concerns: A 42-year-old female presented with a 7-year history of neck pain and a 2-year history of paresthesia and weakness in the upper and lower limbs. The sensations and muscle strength of both upper and lower limbs were decreased. The radiological findings showed that the Pavlov ratios from C3-7 were decreased obviously. Osteophytes as well as spinal cord compression were observed at C4/5, C5/6, and C6/7. Diagnoses: Considering the symptoms and clinical examinations, the patient was diagnosed with cervical stenosis. Interventions: We performed cervical open-door laminoplasty at C3-7 to enlarge the space of the cervical vertebral canal. Outcomes: At the 6-month post-surgery follow-up, the patient showed obvious improvement in paresthesia and weakness in the upper limbs. The cervical disc herniation at C3/4 was aggravated. However, at the 18-month follow-up, the symptoms were relieved, and the herniated cervical disc at C3/4 spontaneously disappeared without any special treatment. Lessons: We suggest that the attachment points of deep muscles in the neck region should be carefully protected during this surgery. Patients who undergo cervical open-door laminoplasty should pay attention to their cervical position and perform neck exercises to train their neck muscles. MRI is an important imaging method to observe dynamic changes in herniated discs for patients with cervical disc herniation.